Renin-Angiotensin System Single Nucleotide Polymorphisms Are Associated with Bladder Cancer Risk. - Samara, Maria; Papathanassiou, Maria; Farmakioti, Ioanna; Anagnostou, Maria; Satra, Maria; Mitrakas, Lampros; Anastasiou, Dimitrios; Chasiotis, Georgios; Christopoulos, Agamemnon; Anagnostou, Athanasios; Christodoulou, Anastasios; Daponte, Alexandros; et al. (Current Oncology, 2021)
The renin-angiotensin system (RAS), besides being a major regulator of blood pressure, is also involved in tumor angiogenesis. Emerging evidence suggests a correlation between the use of pharmacologic RAS inhibitors and a delay in urothelial bladder cancer (BC) progression. However, it is unknown whether RAS gene variants may predispose to the development of BC. This study examined the association of RAS single nucleotide polymorphisms (SNPs) including AT1R rs5186, AT2R rs11091046, REN rs12750834, ANG rs4762, and ANG rs699 with the risk of developing non-invasive BC. Peripheral blood samples from 73 patients with T1 urothelial BC (66 men, seven women) and an equal number of healthy subjects (control group) were collected. The TT genotype of the REN rs12750834 SNP (OR: 2.8 [1.3-6.05], p = 0.008) and to a lesser extent the presence of the T allele (OR: 2.3 [1.2-4.48], p = 0.01) conferred a higher risk of BC. The highest risk for BC within SNP carriers of the RAS system was associated with the presence of the CC genotype (OR: 17.6 [7.5-41.35], p < 0.001) and C allele (OR: 17.7 [8.8-35.9], p < 0.001) of the ANG rs699 SNP. The presence of the AT2R rs11091046 SNP, particularly the AA genotype, was associated with a protective effect against developing BC (OR: 0.268 [0.126-057], p < 0.001). In conclusion, these results support the clinical utility of RAS gene SNPs AT2R rs11091046, REN rs12750834, and ANG rs699 in the genetic cancer risk assessment of patients and families with BC.